#1**+10 **

Look at the first two terms. Form (x + half the coefficient of the 2nd term)^{2}

This is (x + 6)^{2 }which can be expanded as x^{2} + 12x + 36

This, in turn can be written as x^{2} + 12x + 25 + 11, so if x^{2} + 12x + 25 = 0 then x^{2} + 12x + 36 = 11

Or (x + 6)^{2} = 11

x+ 6 = ±√11

x = -6 ±√11

.

Alan
Jun 4, 2015

#1**+10 **

Best Answer

Look at the first two terms. Form (x + half the coefficient of the 2nd term)^{2}

This is (x + 6)^{2 }which can be expanded as x^{2} + 12x + 36

This, in turn can be written as x^{2} + 12x + 25 + 11, so if x^{2} + 12x + 25 = 0 then x^{2} + 12x + 36 = 11

Or (x + 6)^{2} = 11

x+ 6 = ±√11

x = -6 ±√11

.

Alan
Jun 4, 2015